CONCEPTS OF INCOME UNDERLYING ACCOUNTING. - Littleton, A. C. (The Accounting Review, 1937)
Abstract This article discusses concepts of income underlying in accounting. Accounting may seem to be the reader of its literature that is mainly concerned with either the capital statement itself or with the sum available for dividends as determined by two capital elements. The use of no-par stock in the nineteen-twenties, brought two new practices; one was that of crediting to stock account a sum which was less than the full consideration received for newly issued shares; this sum is the so-called "stated capital" and takes the place of the usual credit to capital stock or the full consideration for the shares issued. The other new practice was that of crediting a part of the paid-in assets to a so called paid-in surplus account. Bookkeeping has given quantitative expression to various aspects of profit ever since income and expense accounts have been used, and that has been at least for five hundred years. Managerial policies can be made effective through costs and quantitative measures that are translated into action.